Therapeutic drug monitoring of adalimumab in RA: no predictive value of adalimumab serum levels and anti-adalimumab antibodies for prediction of response to the next bDMARD. Issue 7 (21st April 2020) - Ulijn, Evy; den Broeder, Nathan; Wientjes, Maike; van Herwaarden, Noortje; Meek, Inger; Tweehuysen, Lieke; van der Maas, Aatke; van den Bemt, Bart JF; den Broeder, Alfons A
Abstract : Background: After adalimumab treatment failure, tumour necrosis factor inhibition (TNFi) and non-TNFi biological disease-modifying anti-rheumatic drugs (bDMARDs) are equally viable options on a group level as subsequent treatment in rheumatoid arthritis (RA) based on the current best evidence synthesis. However, preliminary data suggest that anti-adalimumab antibodies (anti-drug antibodies, ADA) and adalimumab serum levels (ADL) during treatment predict response to a TNFi as subsequent treatment. Objective: To validate the association of presence of ADA and/or low ADL with response to a subsequent TNFi bDMARD or non-TNFi bDMARD. Sub-analyses were performed for primary and secondary non-responders. Methods: A diagnostic test accuracy retrospective cohort study was done in consenting RA patients who discontinued adalimumab after >3 months of treatment due to inefficacy and started another bDMARD. Inclusion criteria included the availability of (random timed) serum samples between ≥8 weeks after start and ≤2 weeks after discontinuation of adalimumab, and clinical outcome measurements Disease Activity Score in 28 joints - C-reactive protein (DAS28-CRP) between 3 to 6 months after treatment switch. Test characteristics for EULAR (European League Against Rheumatism) good response (DAS28-CRP based) after treatment with the next (non-)TNFi bDMARD were assessed using area under the receiver operating characteristic and sensitivity/specificity. Results: 137 patients were included. ADA presence was not predictive for response in switchers to a TNFi (sensitivity/specificity 18%/75%) or a non-TNFi (sensitivity/specificity 33%/70%). The same was true for ADL levels in patients that switched to a TNFi (sensitivity/specificity 50%/52%) and patients that switched to a non-TNFi (sensitivity/specificity 32%/69%). Predictive value of ADA and ADL were similar for both primary and secondary non-responders to adalimumab. Conclusions: In contrast to earlier research, we could not find predictive value for response to a second TNFi or non-TNFi for either ADA or random timed ADL.